REWARMING FROM SEVERE ACCIDENTAL HYPOTHERMIA WITH CIRCULATORY ARREST - Brát, Radim; Škorpil, Jiří; Bárta, Jiří; Suk, Marek; Schichel, Tomáš (Biomedical papers, 2004)
This case report demonstrates successful cardiopulmonary and cerebral resuscitation (CPCR) of a young male explored 15 hours following a suicide attempt (carbamazepine intoxication) in deep hypothermia (19°C) with circulatory arrest. An extracorporeal circuit was used to rewarm the patient's blood. Weaning from extracorporeal circulation (ECC) was successful and without complications as was recovery from multiorgan dysfunction, severe rhabdomyolysis and carbamazepine intoxication. An excellent outcome was achieved without any neurological deficit at the time of discharge from the hospital.
Keywords: Hypothermia/Resuscitation/Extracorporeal circulation/Carbamazepine intoxication